Abdominal Aortic Aneurysm (KYAMC Journal, 2021)
Abdominal aortic aneurysm is usually found incidentally. Patient may have vague symptoms of backache, anorexia, dyspepsia. Our patient presented with abdominal pain, dyspepsia, backache. CT scan revealed saccular aneurysm from infrarenal aorta. We decided for laparotomy. A long upper midline incision extending 2.5 cm below umbilicus was made. Gut was mobilized to right side. Inferior mesenteric artery (IMA), the right and left common iliac was taken control. A straight clamp was applied proximal to aneurysm, sac was opened, clot removed. The neck was found and trimmed up to healthy margin. The rent was repaired by a piece of vascular graft. The overlying sac was closed after keeping a drain. Her post operative period was uneventful. She came for follow up with no complain.KYAMC Journal.2021;12(1): 53-55